2006
DOI: 10.1016/j.tetlet.2006.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Suzuki coupling on pyridinium N-(3,5-dibromoheteroar-2-yl)aminides

Abstract: Abstract-A regioselective Suzuki-Miyaura cross-coupling reaction on 3 0 ,5 0 -dibromo pyridinium N-(2 0 -azinyl)aminides is reported. A series of 3 0 -aryl(or heteroaryl)-5 0 -bromo-pyridinium N-(2 0 -pirazinyl)aminides were obtained in good yields. Two isomeric 3 0 ,5 0 -diaryl pyridinium N-(2 0 -azinyl)aminides were also prepared. Ó 2006 Elsevier Ltd. All rights reserved.Functionalization of heterocycles through SuzukiMiyaura palladium-catalyzed cross-coupling has been established as a standard method for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Lastly, to construct central-region-pyrazine arotinoids with a bent overall shape, we selected the position-selective Suzuki reaction of 2-amino-3,5-dibromopyrazine 16 [26,[30][31][32] and boronic acid 3 to prepare 19 (81 %). A subsequent Suzuki coupling with 4-carboxyphenylboronic acid led to 20 in low yield (39 %, Scheme 4); this low yield was due to the compound's instability during the purification step.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, to construct central-region-pyrazine arotinoids with a bent overall shape, we selected the position-selective Suzuki reaction of 2-amino-3,5-dibromopyrazine 16 [26,[30][31][32] and boronic acid 3 to prepare 19 (81 %). A subsequent Suzuki coupling with 4-carboxyphenylboronic acid led to 20 in low yield (39 %, Scheme 4); this low yield was due to the compound's instability during the purification step.…”
Section: Resultsmentioning
confidence: 99%
“…The Suzuki-Miyaura cross-coupling reaction provides an appropriate and practical approach for the synthesis of biaryl compounds, due to its ability to tolerate a wide range of functional groups and good reaction yields [ 3 ]. In the past, pyridine and its derivatives have been used as starting precursors for several useful compounds due to their availability and stability for direct cross-coupling reactions [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. With this approach, Liu and co-workers have described the Suzuki cross-coupling reactions between 2-aryl-1,2,3-triazole- N -oxides and pyridine- N -oxide with good yield of the final products [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reyes et al 117. focused their attention on the palladium‐catalyzed monoarylation of N ‐(3′,5′‐dibromo‐2′‐pyridin‐2′‐yl)pyridinium aminide ( 354 ) with arylboronic acids according to two different protocols ( Procedure A and Procedure B ) (Scheme ) and found that the reaction mixtures of the cross‐couplings contained two monoarylated regioisomers, 355 and 356 , together with the corresponding 3′,5′‐diarylated aminides 357 .…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%